Telemedicine for diagnosis or treatment during Covid-19: systematic review - Melo, Jéssyca Maria França de Oliveira; Garcia, Filipe Reis; Oliveira, Daianny Seoni de; Lanes, Taís Carpes; Junior, Marcos Gabriel do Nascimento; Tiguman, Gustavo Magno Baldin; Ribeiro, Mariane Albuquerque Lima (Online Brazilian Journal of Nursing, 2024)
Objective: To describe the use of telemedicine by health professionals for diagnosis or treatment of patients during the Covid-19 pandemic. Method: This is a systematic literature review of observational studies. Five databases were used. The assessment of the studies methodological quality occurred individually among the revisors and the Joanna Briggs Institute tool was used. Results: The reviewers selected 22 articles from 6,180 works. The services provided through telemedicine were consultation/screening, consultation/follow-up or monitoring, test reports, medication prescriptions and case discussions. The technological resources used were platforms using video and telephone (audio and video). The use of telemedicine made it possible to reduce their exposure to Covid-19, reduce social panic and anxiety, quickly medical specialties access and the possibility of access to diagnosis and treatment of patients with chronic and acute diseases. Conclusion: Telemedicine can be an important tool in healthcare, keeping patients and healthcare professionals safe during the Covid-19 pandemic.